Unit Linked Life Insurance Premium Reserve Modification Using Fackler and Point to Point Methods - Sheren Rosari Monica Rachmad; Tohap Manurung; Chriestie E.J.C Montolalu (Jurnal Ilmiah Sains, 2023)
The present study aims to investigate the use of the Fackler method in determining the reserve of unit-linked whole life insurance premiums. Unit-linked whole life insurance combines both protection and investment features, and to mitigate liquidity risks, it is crucial for the insurer to establish reserves. The insurer limits the value of the benefits obtainable through a minimum guarantee and stamp value to counteract losses that may arise due to fluctuations in share prices.The Fackler method is employed to calculate the reserve of unit-linked whole life insurance premiums by determining the cash value of annuities using a fixed interest rate in conjunction with the Indonesia Mortality Table 2019. Subsequently, an annual net premium is calculated. The calculation of the annual net premium necessitates the determination of a single net premium, which is computed using the Point to Point method with the result is . The outcome of this calculation yields the reserve value for a 40-year-old individual. It is noteworthy that the reserve value will increase with the lifespan of the individual or the duration of the policy contract. Keywords : Fackler method;  premium reserves; Unit-linked